Factors of the childbirth fear among nulliparous women in Iran - Safieh Kananikandeh; Farkhondeh Amin Shokravi; Mojgan Mirghafourvand; Shayesteh Jahanfar (BMC, 2022)
Abstract Background Fear of childbirth is an anxiety associated with childbirth, which manifests itself in physical and concentration problems. It is often associated with requesting a cesarean section, and it is prevalent in nulliparous women. This is a study aimed to summarize the published research on the factors for fear of childbirth in nulliparous women in Iran. Methods This study was conducted based on the PRISMA statement. A literature search was performed on nine electronic databases (Web of Sciences, Since Direct, Scopus, PubMed, Cochrane Library, ProQuest, and Persian databases including Scientific Information Database, Irandoc, and Magiran) using keywords related to fear of childbirth, factors, nulliparous, and Iran from 2000 to 2020. This study included cross-sectional studies with full-text in English or Persian in Iran. The quality of the selected studies was evaluated independently by two authors and via the STROBE checklist. Results In this study, 93 articles were identified,13 duplicate articles were excluded, 80 articles were screened by title and abstract, 62 were excluded, and the full-text of 18 articles was assessed for analysis. Of these, 12 were excluded, and six articles were reviewed. Six studies were conducted in different provinces of Iran. Based on the study results, factors of the fear of childbirth in nulliparous women were: biological (the process of labor and childbirth and labor pain, concern for the baby (harm to the baby and baby infirmity), psychological (painful injections during labor and suturing in childbirth), and individual (loss of control during labor). Conclusions This study identified four main factors that affect fear of childbirth status in nulliparous women, and concern for the baby was a more common factor in this study. In conclusion, these factors can be reduced by increasing their assurance about child health, training during pregnancy, talking about positive experiences, and holding workshops.